2015
DOI: 10.1111/jdv.13451
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitive atopic dermatitis – a neglected subset: Clinical, laboratory, histological and photobiological workup

Abstract: PhAD is an underreported subset of atopic dermatitis, which is rarely diagnosed. This study suggests that several features including atopic diathesis, eczematous lesions in UVR exposed body regions and positive photoprovocation reaction are suggestive of PhAD as the likely diagnosis. Typically, the atopic eczema starts without a sign of photosensitivity, however, in a subgroup of AD patients after a few months to years, a switch occurs leading to PhAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 21 publications
2
26
1
1
Order By: Relevance
“…It is believed that the majority of CAD patients have photoallergy and contact allergy, often to airborne allergens, such as fragrances, plant antigens and medication 8,9 . Ellenbogen et al 10 . proposed the concept of photosensitive atopic dermatitis, the clinical features of which include atopic diathesis, eczematous lesions in UV radiation‐exposed body regions and positive photoprovocation reactions, which may be misdiagnosed as CAD.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the majority of CAD patients have photoallergy and contact allergy, often to airborne allergens, such as fragrances, plant antigens and medication 8,9 . Ellenbogen et al 10 . proposed the concept of photosensitive atopic dermatitis, the clinical features of which include atopic diathesis, eczematous lesions in UV radiation‐exposed body regions and positive photoprovocation reactions, which may be misdiagnosed as CAD.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of AD patients benefit from UV radiation therapy and from exposure to the sun in a controlled natural setting [11,12]. However, an estimated 10% of patients are reported to show photoaggravation [13]. At least two studies from Japan have reported patients with AD who suffer from recalcitrant facial erythema related to sun exposure [14,15].…”
Section: Ultraviolet (Uv) Radiation and Skin Barrier Dysfunctionmentioning
confidence: 99%
“…Also, some skincare products and comorbidities such as polymorphous light eruption could mask or worsen the sensitivity to UV radiation [17]. In a retrospective analysis of 17 patients with longstanding AD who suddenly developed photosensitivity to UVA, the onset of photosensitivity was reported during spring and summer and during exposure to artificial UVR as part of the patients' treatment regimen [13].…”
Section: Ultraviolet (Uv) Radiation and Skin Barrier Dysfunctionmentioning
confidence: 99%
“…Im Laufe der Jahre hat sich so eine sehr fruchtbare wissenschaftliche Interaktion herausgebildet mit zahlreichen Forschungsaufenthalten in beiden Ländern. Eine Auswahl daraus entstandener Veröffentlichungen ist in der Literatur widergegeben .…”
Section: Abbildungunclassified